Utilizing social emotional learning to increase the learning motivation of elementary school - Isnaini, Isnaini; Indaryanti, Indaryanti; Dakim, Dakim (Universitas Riau Kepulauan, 2023)
This article reports a study that applies Social Emotional Learning (SEL) to increase the learning motivation of class III.B students at SD Negeri 94 Palembang. SEL is a learning process that aims to recognize and process emotions and build good relationships with others and be able to make responsible decisions. Meanwhile, learning motivation is the drive that a person has to achieve a goal, indicated by changes in attitudes, skills, and understanding. This research uses Classroom Action Research (CAR) using the Kemmis and Mac research design models. Taggart. The research subjects totaled 24 students, consisting of 15 boys and 9 girls. The general description of learning motivation in pre-cycle only reaches 40.63% which is relatively low. Whereas in cycle I there was an increase reaching a percentage of 64.67% which was classified as moderate. Continuing in cycle II, learning motivation increased to 72.93% and was classified as moderate. Up to cycle III there was an increase of up to 81.25% which was relatively high. This proves that there is an increase in the learning motivation of class III.B students at SD Negeri 94 Palembang by implementing Social Emotional Learning (SEL).